Optical Nanofiber Skins for Multifunctional Humanoid Tactility. (18th January 2023) - Tang, Yao; Yu, Longteng; Pan, Jing; Yao, Ni; Geng, Weidong; Li, Xiong; Tong, Limin; Zhang, Lei; Zhang, Zhengyou; Song, Aiguo
Abstract : Humanoid tactility has been boosting robotic intelligence in object recognition, dexterous manipulation, and human–robot interaction. For many artificial tactile sensors, especially those based on optical principles, inflexibility, bulkiness, and monomodality limit their potential to function as humanoid skins. Herein, by embedding lab‐made optical nanofibers (ONFs) into elastomeric films, soft, flexible, thin (around 500 μm, similar to human skin), and multimodal (force and thermosensitive) robotic skins are achieved. These superior characteristics arise from the low flexural rigidity and large evanescent field of ONFs, due to their subwavelength diameters (down to 450 nm). By tuning light wavelength, ONF diameter, and skin thickness, variable sensitivities and sensing ranges for both force and temperature are reported. Depending on different sensing requirements, special modules can be further assembled on the ONF skins for various surface properties, including hardness, texture, and thermal conductivity. The ONF skins can enable a commercial robot to emulate human behaviors, including adaptive grasping of flimsy objects, contactless temperature measurement, and even the perception of leaf veins. It is anticipated that these ONF skins could offer a unique solution in multiple intelligent systems such as robotics, prosthetics, human–machine interface and wearable devices. Abstract : By embedding the optical nanofibers (ONF) into elastomeric films, multimodal artificial skins that can respond to temperature and force stimuli are achieved. Special modules are further assembled on the ONF skins to recognize material properties including hardness, texture, and thermal conductivity. Commercial robots equipped with the ONF skins perform human‐like actions based on the tactile sensing capabilities.